Biocompatible Autonomic Self‐healing PVA‐TA Hydrogel with High Mechanical Strength. Issue 13 (11th June 2021) - Huang, Jinxin; Wu, Chengwei; Yu, Xiaogang; Li, Heng; Ding, Shuaiwen; Zhang, Wei
Abstract: The autonomic self‐healing hydrogel with good biocompatibility is generally poor in tensile strength, which seriously hinders its development and application in the field of loaded biomaterials. Here, based on a large number of strong H bonds formed between poly(vinyl alcohol) (PVA) and tannic acid (TA), an autonomic self‐healing PVA‐TA hydrogel with high strength and high healing efficiency is successfully prepared. The tensile strength of PVA‐TA hydrogel is 224 kPa, which can spontaneously restore to 87% of its initial strength within 2 h after fracture without external stimuli. The obtained hydrogel also shows good biocompatibility. Abstract : The autonomic self‐healing hydrogel with good biocompatibility is generally poor in tensile strength. Here, based on lots of H bonds formed between poly(vinyl alcohol) (PVA) and tannic acid (TA), a high‐strength self‐healing PVA‐TA hydrogel with high healing efficiency is prepared. The tensile strength of PVA‐TA hydrogel is 224 kPa, which spontaneously restores to 87% in 2 h without external stimuli.